Teaching the Narrative Texts Using Animation Video: Raising Students’ Skills on Reading Comprehension - Siti Munawaroh (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2019)
This study aims to answer the problem of whether animated videos improve reading skills in understanding language features, find real and detailed information, and take moral values in narrative texts in the classroom. The author uses classroom action research. The tools used to collect data are observation sheets, field notes, and tests. In cycle one to cycle three, the author uses animated videos as a medium to improve reading comprehension in understanding language features, finding real and detailed information, and taking moral values in narrative texts. The author uses animated videos with the activity of showing printed images of animated video stories and giving unknown words to improve students' ability to understand the narrative text language features. The author uses animated videos with predictive activities, confirmations, class discussions, and tests to improve students' ability to find real and detailed information. The author uses animated videos by reviewing each character and finding real and detailed information to improve students' ability to take moral values from narrative texts.